Evaluation of the effects of september hunting seasons on Canada geese in Nebraska - Scott R. Groepper; Mark P. Vrtiska; Larkin A. Powell; Scott E. Hygnstrom (Wildlife Society Bulletin)
Abstract Populations of temperate‐nesting Canada geese (Branta canadensis) have increased in Nebraska, USA, resulting in an increased number of nuisance and damage complaints. September hunting seasons were initiated in southeastern Nebraska in 2004 to reduce populations of Canada geese. We analyzed band recoveries from Canada geese banded in southeastern Nebraska during their hatch‐year (HY) or after‐hatch‐year (AHY) to determine whether September hunting seasons affected survival, harvest, and recovery rates. Survival analyses revealed that HY geese had higher survival than AHY geese (SAHY = 0.696, 95% CI = 0.679–0.713; SHY = 0.896, 95% CI = 0.786–0.953) and September seasons did not affect survival of geese in southeastern Nebraska. Geese banded in the geographic zone with the September seasons (southeastern Nebraska) had the same survival as did geese outside the hunt zone (northeastern Nebraska; S = 0.711, 95% CI = 0.666–0.752). September hunting seasons affected timing of band recovery; 23–49% of annual band recoveries occurred during the month of September. Prior to the initiation of the September seasons, the highest percent of recoveries occurred during November. The September seasons appeared to temporally redistribute harvest but did not reduce survival for populations of Canada geese in southeastern Nebraska. Continuation of the season may not be warranted, because management does not appear to be affecting AHY survival, which is needed to reduce the population. Additional or new methods are likely needed to control populations of temperate‐nesting Canada geese in Nebraska and managers should evaluate the effectiveness of these methods as they are implemented. © 2012 The Wildlife Society.